Legacy phosphorus under long-term soil and fertilizer management in crop production - Coelho, Marta Jordana Arruda (2019)
Phosphorus (P) is the second macronutrient that most limits the agricultural production due to its low level of availability in the soils, thus requires high demand to obtain high crops efficiency in the short-term, however, it is a non-renewable resource. In long-term, differents P fertilizer placement can effect, particularly the preferential forms of P retained and legacy in the soil pool and their contribution to increasing P use efficiency by crops over time. In this context, in the present thesis, in the chapter two, we aimed to assess changes in soil P pools (labile, moderately labile and non-labile) and legacy soil P accumulation after long-term P fertilization with an initial soil P buildup and annual P applications. P pools in the soil showed a significant effect of P application on labile P fractions with the adoption of annual rates of 60, 90 and 120 kg P2O5 ha-1, while effects of the initial P application were less significant for this tropical high weathered soil. Thus, P accumulation from annual rates in the labile fractions of P could help to improve the soil legacy P availability and represent a profitable strategy to reduce large inputs of inorganic P fertilizer in tropical crop production systems. in the chapter three, we evaluated the influence of long-term P fertilizer placement on soil P pools and legacy soil P accumulation under a corn-soybean long-term rotation. Significant changes in soil P pools were observed by the long-term effect of P fertilizer placement. Broadcast P fertilizer placement increased the labile P and moderately labile P in the topsoil (0-7.5 cm), and had a greater P fertilizer use efficiency compared to deep band placement. The use of combined placement strategies will contribute to maintain the available P pools maximizing P fertilization efficiency in reduced tillage systems. in the chapter four, we evaluated the effects of long-term P fertilizer placement (initial placement and annual rates and placement of P) in the transition of pasture to double-crop of soybean and corn under no-till crop production on changes in the soil P pools and legacy soil P accumulation. Results of P pools in the soil showed a significant effect of P application on labile P fractions in soil surface with the adoption of annual rates and placement of 100B and 100SP kg P2O5 ha-1 under all initial P application, and 100B for the all others P fractions and soil depths, while effects of the initial P application were less significant for this tropical high weathered soil. Thus, P accumulation from the initial (P remains in the soil after five years) and annual P fertilizer application in the labile P pools could help (at least in part) to reduce current high dependency and large inputs of inorganic P fertilizer in tropical no-till systems.